On the cobalt and cobalt oxide electrodeposition from a glyceline deep eutectic solvent - Sakita, Alan M. P. [UNESP]; Della Noce, Rodrigo; Fugivara, Cecílio S. [UNESP]; Benedetti, Assis V. [UNESP] (Royal Society of Chemistry (RSC), 2016)
The electrodeposition of cobalt and cobalt oxides from a glyceline deep eutectic solvent is reported. Cyclic voltammetry, chronoamperometry, scanning electron microscopy, and Raman spectroscopy are employed to study the Co deposition processes. Surface analysis reveals that metallic cobalt is deposited at potentials less negative than the current peak potential whereas cobalt oxides are detected and electrochemically observed when the deposition is done at more negative potentials. i-t transients are analyzed by applying the Scharifker and Hills (SH) theoretical model. It is concluded that cobalt deposition occurs via a progressive nucleation and growth mechanism for concentrations higher than 0.05 mol L-1 cobalt ions. For concentrations ≤0.025 mol L-1 cobalt ions and low overpotentials, the mechanism changes to instantaneous nucleation. The im-tm relationships of the SH model are used to determine the values of the kinetic parameters and the cobalt ion diffusion coefficient.